Natural selection its place in modern society. - Mark Pearce; Michael De Robbio; James Liotta; Mark A Elgar; Graham Flannery (Bendigo, Vic. VEA, 2008)
Offers a brief explanation of natural selection, how it has affected human evolution and how it is continues to affecting daily living through, for example, genetic engineering or global warming.
"English captions for the deaf and hearing impaired"--Container. "Its place in modern society"--Container subtitle.
Writer/director, Mark Pearce; producer, Michael De Robbio.
Presenter, James Liotta; with scientists Mark Elgar and Graham Flannery
Closed captioned and audible description
Keywords: Natural selection; Evolution (Biology)